Paragogy and flipped assessment: experience of designing and running a MOOC on research methods. (3rd May 2016) - Lee, Yenn; Rofe, J. Simon
Abstract: This study draws on the authors' first-hand experience of designing, developing and delivering (3Ds) a massive open online course (MOOC) entitled 'Understanding Research Methods' since 2014, largely but not exclusively for learners in the humanities and social sciences. The greatest challenge facing us was to design an assessment mechanism that was (i) rigorous yet practicable at scale, vis-à-vis over 60, 000 students from highly diverse backgrounds; (ii) compatible with the pedagogical orientation of the MOOC provider; and (iii) meaningful to the nature of the course subject. Based on a network analysis of forum interactions and a qualitative analysis of a random sample of 116 research questions proposed by students, we explore how participants' understanding of research methods developed through a series of carefully sequenced 'e-tivities' and 'open peer assessments' over the duration of the course. The aim of this study was to consider a model of 'flipped' assessment, drawn from elements of 'paragogy' and the IR Model that acknowledges and exploits peer learning opportunities that are not routinely captured by completion statistics.